RESPONS PERTUMBUHAN DAN KUALITAS BEBERAPA VARIETAS KENAF (Hibiscus cannabinus L.) TERHADAP PEMBERIAN PUPUK N DAN KOTORAN AYAM - Hadi Pranoto (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
The reaserch was conducted to analizies the interaction of the responsibilities of varieties, N and chicken manure fertillizer, analizies of varieties treatment, analizies dosage of  N and chicken manure fertilizer to growth, yield an quality of kenaf fiber. The design of the reaserch used (split-split plot design) in a Randomized Block Design (RBD) factorial. The main plot is Nitrogen fertilizer (N), sub plot is chicken manure fertilizer and the sub-subplot is kenaf varieties (V). The all treatment was repeated in three replication. The numbers of plants in the reaserch are 2.700 units. Plot square is 2,25 meter square respectively. The results showed, the interaction have occured 75 after plantig  days  on the plant higest. Nitrogen fertilizer (30 gram urea/plot) after  manure fertilizer (3.380 gram chicken manure fertilizer/plot), KR-14 variety, the weight of wet and dry roots. The best kenaf fiber quality is white (7,20%). The best chemistry composition of kenaf fiber is KR-14 too.  The higest average of fiber strenght showed combination of 40 gram urea dosage/plot, 3.380 gram chicken manure/plot and KR-14 treatment whith value 206 mf/g.